Diagnostic Utility of Endocan and Interleukins for Late-Onset Neonatal Sepsis - Preslava Gatseva; Alexander Blazhev; Zarko Yordanov; Victoria Atanasova (Journal of Biomedical & Clinical Research)
The aim of this study was to determine the potential of early inflammatory markers to diagnose late-onset neonatal sepsis – interleukin 6 (IL-6), interleukin 8 (IL-8) and endocan (ESM-1), and to compare them with routinely used markers like C-reactive protein (CRP) and procalcitonin (PCT). A prospective (January, 2022 – January, 2023) clinical-epidemiological study was conducted in a third level NICU in Pleven, Bulgaria. Patients with suspected nosocomial infection and healthy controls were tested. A sandwich ELISA method was used to measure the serum concentrations. Sixty newborns with an average gestational age of 29.75±3.61 gestational weeks were included, of which 35% were symptomatic and infected, 33.3% were symptomatic but uninfected, and 31.7% were asymptomatic controls. The mean values of PCT and IL-6 differ significantly in the three groups. For ESM-1, IL-8 and CRP, the difference was statistically insignificant. The best sensitivity (78%) and negative predictive value (84%) was found for IL-6. The introduction into routine practice of indicators such as PCT and IL-6 may provide an opportunity to promptly optimize the diagnostic and therapeutic approach to LOS.